Perkembangan Motorik Bayi dan Implikasinya pada Konsep Pendidikan Islam: Baby’s Motoric Development and its Implications for Islamic Education Concept - Meriyanti Meriyanti; Ermis Suryana; Kasinyo Harto (Al-Musannif, 2023)
Motoric development in babies is very important; unfortunately, sometimes parents, as the closest family, do not provide enough stimulation to educate them. This study aims to analyze the infant's motoric development and its implications for Islamic education. Baby's motoric development consists of gross and fine motors; these two motors must develop normally according to their age. So the implications start with parental education, family roles, and the environment, which is very important for a baby's motoric development. This research uses library research with a qualitative approach, which comes from journals, articles, and books. The results of the analysis discuss that motor development is the most important thing for infants because infancy is a golden period that passes quickly and will not be repeated. In addition, this study explains the implications of infant motor development on the Islamic education concept, which affects mothers, families, and the environment, in addition to the urgency of infant motor stimulation.